Effects of hot air treatment on the quality attributes of semidry-milled Indica rice. (January 2018) - Ren, Meng-Ying; Tong, Li-Tao; Li, Xianghong; Xie, Ding; Wang, Lili; Zhou, Xianrong; Zhong, Kui; Liu, Liya; Zhou, Sumei; Yi, Cuiping
Abstract: To investigate the effects of hot air treatment (HAT) on the quality attributes of Indica rice semidry-milling, HAT was applied at various temperatures (45–120 °C) and processing times (0–240 min). The changes in grain-surface cracking, moisture absorption rate, damaged starch, rheological properties, microbial decontamination, and texture qualities were evaluated. HAT induced many cracks in the rice grains, shortening the soaking time to reach maximum water content (28%) to 8 min. However, at high temperatures, extending the HAT time slowed the water absorption rate. Under the optimum HAT conditions and soaking time, the total viable counts in the rice flour were similar to those of dry-milled rice flour (10 2 –10 3  cfu/g), with no coliforms and few yeasts and molds. The damaged starch content, rheological and texture properties were similar to those of wet-milling. Therefore, an appropriate HAT can shorten the soaking time of the rice and clean it during the milling process. Highlights: Soak time of indica rice in semidry milling is reduced by hot air treatment (HAT). HAT inhibits bacterial growth in indica rice flour. HAT semidry-milled and wet-milled indica rice are of similar quality.